RP-HPLC Method for the Estimation of Lamivudine in Bulk and Pharmaceutical Dosage Forms - SHANTA KUMARI, A.; PRAKASH, K.; NAGOJI, K.E.V.; RAO, M.E.B. (Asian Journal of Chemistry, 2010)
A new reverse phase high performance liquid chromatographic (RPHPLC) method was developed for the estimation of lamivudine (3TC) in bulk and pharmaceutical dosage forms using RP-C18 column using an isocratic HPLC system. The mobile phase consisted of acetonitrile and 0.05 M potassium dihydrogen phosphate (pH 4.2) in the ratio of 50 : 50 at a flow rate of 1 mL/min. The run time was 15 min. Nelfinavir mesylate (NEM) (50 μg/mL) was used as internal standard. The detection was carried out at 271 nm and the linearity was found to be in the range of 0.5-160 μg/mL. The retention times for drug (3TC) and internal standard (NEM) were 3.342 and 12.833 min, respectively. Recovery studies shown that about 100.07 % of 3TC could be recovered from the pre-analyzed samples indicating high accuracy of proposed method. There was no intra-day and inter-day variation found in the method of analysis. The mean drug content in branded 3TC tablet dosage forms was quantified and found to be between 99.79 and 100.86 %.